Komposisi Tubuh dan Kesegaran Kardiovaskuler yang Diukur dengan Harvard Step Test dan 20m Shuttle Run Test pada Anak Obesitas - Maria Mexitalia; MS Anam; Azusa Uemura; Taro Yamauchi (MEDIA MEDIKA INDONESIANA, 2012)
Body composition and cardiovascular fitness measured by Harvard step test and 20m shuttle run test in obese childrenBackground: One of the impacts of obesity are physical and cardiovascular problems. Harvard step test and 20m shuttle run test can be used to measure cardiovascular fitness. Objective of this research is to determine the association between body composition with cardiovascular fitness in obese children measured by Harvard step test (HST) and 20m shuttle run test (SRT).Method: Cross sectional study was conducted to 31 students of Bernardus Elementary School Semarang in August 2010. Body composition (body mass index/BMI and fat percentage) was measured by Tanita BC545. Cardiovascular fitness was measured by HST and 20m SRT. During the step test Polar Vantage? Heart Rate (HR) monitor was attached to the subjects. Data were analyzed with Spearman correlation.Result: The average age was 10.7 (0.68) years. Only 17 children finished level III of Harvard test. The HR recovery never met the normal limit. There was no difference of physical fitness index (PFI) level I, II, and III (p=0.130) but the HR recovery decreased significantly (p=0.020). The mean of VO2max measured by 20m SRT was 20.5 (1.2) ml/kg/min, significantly lower compared with HST 24.2 (2.27) ml/kg/min. There were negative correlation between PFI and BMI (r=-0.381; p=0.034) and VO2max and BMI(r=-0.448; p=0.012).Conclusion: There are negative correlation between body mass index and cardiovascular fitness. However there are difference result of VO2max from Harvard step test comparing with 20m shuttle run test.Keywords: Harvard step test, 20m shuttle run test, physical fitness, obesityABSTRAKLatar belakang: Salah satu dampak obesitas adalah masalah fisik dan kardiovaskuler. Harvard step test (HST) dan 20m shuttle run test (SRT) merupakan tes yang digunakan untuk mengukur tingkat kesegaran kardiovaskuler. Tujuan penelitian adalah mengetahui hubungan komposisi tubuh dengan tingkat kesegaran kardiovaskuler pada anak obesitas menggunakan HST dan 20m SRT.Metode: Penelitian belah lintang dilakukan di SD Bernardus Semarang bulan Agustus 2010. Komposisi tubuh (indeks massa tubuh/ IMT) dan persentase lemak tubuh diukur dengan Tanita BC545. Dilakukan Harvard step test dan denyut jantung selama tes direkam menggunakan Polar Vantage Heart Rate (HR) monitor, serta dilakukan 20m SRT. Data dianalisis dengan uji korelasi Spearman.Hasil: Tiga puluh satu anak obesitas berumur 10,7(0,68) tahun mengikuti penelitian ini. Hanya 17 anak yang bisa menyelesaikan tes Harvard sampai tahap III. Didapatkan rerata HR saat istirahat lebih tinggi dibanding normal. Tidak didapatkan perbedaan physical fitness index (PFI) antara tes I, II, dan III (p=0,130) tetapi didapatkan penurunan HR recovery I, II, dan III yang bermakna (p=0,020). Rerata VO2max SRT 20,5(1,2) ml/kg/menit lebih rendah secara bermakna dibandingkan HST I yaitu 24,2(2,27) ml/kg/menit. Didapatkan hubungan terbalik antara PFI dengan IMT (r=-0,381, p=0,034) dan VO2max dengan IMT (r=-0,448, p=0,012).Simpulan: Didapatkan hubungan terbalik antara indeks massa tubuh dengan kesegaran kardiovaskuler pada anak obesitas, tetapi tidak didapatkan kesesuaian VO2max berdasarkan Harvard step test dan 20m shuttle run test.